2021
DOI: 10.1038/s41467-021-23710-y
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral synthesis of nano-metalchelate for tumor catalytic therapy by ligand field-enhanced coordination

Abstract: The iron gall ink-triggered chemical corrosion of hand-written documents is a big threat to Western cultural heritages, which was demonstrated to result from the iron gall (GA-Fe) chelate-promoted reactive oxygen species generation. Such a phenomenon has inspired us to apply the pro-oxidative mechanism of GA-Fe to anticancer therapy. In this work, we construct a composite cancer nanomedicine by loading gallate into a Fe-engineered mesoporous silica nanocarrier, which can degrade in acidic tumor to release the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 40 publications
0
59
0
Order By: Relevance
“…1,2 Recently, a variety of nanoparticles have been proved holding biological and physical benefits, including elevated selectivity, enhanced efficacy, and minimized toxicity. 3,4 Thus, ever-increasing attentions have been attracted in construction of functional nanoparticles for application in cancer theranostics, involving polymers, liposomes, and inorganic nanostructures. [5][6][7] Among these designs, carbon dots (CDs) possess great promises thanks to their tunable optical properties, superior biocompatibility, easy surface modification, and most importantly, phototriggered photothermal therapy (PTT) and photodynamic therapy (PDT) potentials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Recently, a variety of nanoparticles have been proved holding biological and physical benefits, including elevated selectivity, enhanced efficacy, and minimized toxicity. 3,4 Thus, ever-increasing attentions have been attracted in construction of functional nanoparticles for application in cancer theranostics, involving polymers, liposomes, and inorganic nanostructures. [5][6][7] Among these designs, carbon dots (CDs) possess great promises thanks to their tunable optical properties, superior biocompatibility, easy surface modification, and most importantly, phototriggered photothermal therapy (PTT) and photodynamic therapy (PDT) potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomedicine refers to the combination of nanotechnology with biomedical and pharmaceutical sciences, aiming to innovate in the healthcare of patients via exploiting imaging and therapeutic agents with enhanced efficiency and improved safety 1,2 . Recently, a variety of nanoparticles have been proved holding biological and physical benefits, including elevated selectivity, enhanced efficacy, and minimized toxicity 3,4 . Thus, ever‐increasing attentions have been attracted in construction of functional nanoparticles for application in cancer theranostics, involving polymers, liposomes, and inorganic nanostructures 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is a new therapy strategy being used in the treatment of many diseases. The use of nanocarriers to support immune responses has become imperative in cancer therapy ( 163 ). This is because barriers created by the tumor and the presence of cocktails of protein and chemicals in tumor microenvironments induce immune cell reprogramming, which undermines their ability to fight tumors and reduce cancer cells population ( 164 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NP) have been widely explored as carriers of small molecule chemicals and biomolecules. 21 , 22 , 23 , 24 , 25 , 26 Recent studies have demonstrated their superior advantages in the delivery of functional nucleic acids including short interfering RNA (siRNA), viral RNA mimics, and CpG ODNs. As an example, a tumor microenvironment‐responsive nanobooster encapsulates a hybrid RNA encoding both siRNA and viral RNA signature for orchestrated activation of innate immunity and potent induction of long‐term T cell memory, eliciting multilayer antitumor activities.…”
Section: Introductionmentioning
confidence: 99%